2020
DOI: 10.1111/jfpe.13585
|View full text |Cite
|
Sign up to set email alerts
|

Sequential valorization strategies for dairy wastewater and water hyacinth to produce fuel and fertilizer

Abstract: To overcome the obstacles of treatment of dairy wastewater (DW) under anaerobic mono‐digestion and sustainable disposal of harvested water hyacinth (WH) a novel sequential valorization strategy was adopted to obtain fuel and fertilizer. Initially, DW and WH were subjected for anaerobic co‐digestion to elucidate the synergistic effect of the substrates to improve the process efficiency and increased biomethane production. The results indicated that the co‐digestion mixture (DW: WH‐1:1) has resulted in biomethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
0
9
1
Order By: Relevance
“…6%, w/w) and volatile solid content (97.3%, w/w) of WH indicates that the structural components cellulose and hemicellulose are highly available as raw materials for biorefinery and bio-based conversion routes. As reported, based on the season of harvest, geographical location and the plant cell wall maturity, the relative composition of the structural and elemental characteristics of WH in this present study varies slightly with the previous studies [24,25,45,46].…”
Section: Biochemical Characterization Of Water Hyacinthcontrasting
confidence: 56%
See 1 more Smart Citation
“…6%, w/w) and volatile solid content (97.3%, w/w) of WH indicates that the structural components cellulose and hemicellulose are highly available as raw materials for biorefinery and bio-based conversion routes. As reported, based on the season of harvest, geographical location and the plant cell wall maturity, the relative composition of the structural and elemental characteristics of WH in this present study varies slightly with the previous studies [24,25,45,46].…”
Section: Biochemical Characterization Of Water Hyacinthcontrasting
confidence: 56%
“…Widespread of this biomass on water surface has created numerous ecological problems like destruction of aquatic flora and fauna, irrigation problems as well as caused several vector borne diseases in humans [21,22]. Thus, the demand for eradication and valorization of WH has grown rapidly in recent years and resulted in its various applications like biomanure [22], bioethanol [18,23] and biogas production [24,25]. However, utilization of WH for yeast based lipid production has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…This study indicated the feasibility of sustainable valorization of WH-derived liquid hydrolysate towards a biorefinery framework Alankar et al (2021). By the way, Arutselvy et al (2020), have conducted a sequential valorization strategy for dairy wastewater (DW) and WH to produce fuel and fertilizer. Anaerobic co-digestion of WH and DW improved the process efficiency and increased biomethane production.…”
Section: Valorization Of Whmentioning
confidence: 97%
“…Co-digestion of diverse bio-waste streams like harvested water hyacinth and dairy wastewater, tested by [69], also yielded a wide range of bio-products, quite like in [108]. Even the leachate from the organic fraction of municipal solid wastes (MSW)-be it from collection trucks or landfills-which is looked upon as nothing other than an environmental menace, can be the source of medium-chain fatty acids [109].…”
Section: Municipal and Industrial Solid Waste And Sewage Managementmentioning
confidence: 99%